УДК 378.147 ВИРТУАЛДЫ ШЫНДЫҚ. БІЛІМ БЕРУ САЛАСЫНДАҒЫ ЖАҢА ТЕХНОЛОГИЯЛЫҚ ӘЗІРЛЕМЕЛЕРДІ ПАЙДАЛАНУ - Оразымбет, Муслим; Turganbaeva, Alma (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
In this publication, the reasons for the spread of virtual reality technologies in the field of education, the classification of virtual reality technologies and their functionality, and the applications of virtual reality technologies used in the education of future architects are presented.These attributes of modernity expand the understanding of technology in education, which so far includes distance learning, electronic technologies, mobile applications, and e-textbooks. Taking into account the new technological realities, it is necessary to consider the necessary changes in the content of education, the management of the learning process should also approach the indicators of online interaction.